HUBUNGAN TINGKAT PENGETAHUAN MURID SD TERHADAP PERILAKU PENCEGAHAN KARIES GIGI : LITERATUR REVIEW - Winarni, Lastri Mei; Wibisono, H.A.Y.G; Nurfaizah, Ismi (Jurnal Nusantara Mandani, 2023)
Background: Caries occurs due to the process of demineralization of the hard tissues of the teeth followed by the destruction of dental organic matter. The problem of dental caries is vulnerable to relation to children who are still in elementary school. Where elementary school children still have minimal knowledge of dental hygiene. Knowledge is very important in underpinning the formation of behaviors that support children's dental and oral hygiene. Objective: To determine the relationship between elementary school students' knowledge of the prevention of dental caries. Subject and Methods: The writing method used is literature review or literature study by collecting 15 articles from online search engine journals such as PubMed and Google Scholar. Results: The results show that (1) parents' knowledge about caries prevention in elementary school students can be seen based on their diet and visits to the dentist; (2) behavior plays an important role in influencing dental and oral health status. In addition to directly affecting dental and oral health status, behavior can also affect environmental factors and health services; (3) the behavioral relationship regarding the behavior of preventing dental caries in children is reviewed based on knowledge. Conclusion: Healthy behavior is manifested in actions to maintain and maintain health, including disease prevention and personal hygiene, especially for the prevention of dental caries.